Quality assurance practices as drivers for technical - vocational education and training’s transformation in Zimbabwe - Pinias Chikuvadze; Samuel Mugijima; Mutseekwa Christopher; Zuva Joseph (Edukasi, 2025)
Background - This paper was motivated by the relevance of quality assurance (QA) in enhancing the quality of instruction in Technical and Vocational Education and Training (TVET).  It is in this context that we sought to gain insight into the function of QA procedures in catalysing the transformation of TVET in Zimbabwe, with a focus on the opportunities and challenges.   Research Urgency - QA is crucial in transforming Zimbabwe’s TVET system to meet global standards and close skills gap. Thus, strengthened procedures will align TVET with industry needs and drive economic development.  Research Objectives - The purpose of the study is to examine the role of QA procedures as a catalyst in transforming Zimbabwe’s TVET system for improved effectiveness and relevance. Research Method - To gain an all-inclusive view of the issue under investigation the researchers opted to ground this paper in a systematic review approach. In this respect, the PRISMA 2020 checklist guaranteed uniformity and transparency in choosing the 50 sources from carefully chosen databases (WoS, DOAJ, and Scopus). The finding revealed that in TVET programmes QA procedures were implemented through curricula development, accreditation, and assessment. Research Findings - Based on the results, it was revealed that in TVET programmes, QA procedures were implemented through curricula development, accreditation, and assessment. From the findings it was noted numerous opportunities existed in TVET programmes to enhance the implementation of QA procedures. Additionally, this paper identifies the challenges, such as resource limitations, the need for continuous professional development, and the configuration of TVET outputs with job market demands. Conclusion - It can be concluded that QA procedures are an essential catalyst for the transformation of TVET in Zimbabwe. Thus, by embracing opportunities for improvement and leveraging best procedures, Zimbabwe can develop robust TVET programmes capable of producing competent human capital ready to meet the evolving industry's needs. Research Novelty/Contribution - This paper uniquely frames QA procedures as a transformative catalyst in Zimbabwe’s TVET system, linking it to industry relevance and national development agenda, an under-explored area in local research.